Site-specific excision from RNA by RNase H and mixed-phosphate-backbone oligodeoxynucleotides. - Agrawal, S (1990)
Oligodeoxynucleotides containing phosphodiester or modified internucleoside linkages were investigated with respect to their ability to be acted on by ribonuclease H activities present in a HeLa cell nuclear extract after hybridization with complementary sequences in RNA. Oligodeoxynucleotides complementary to nucleotides 2-14 of human U1 small nuclear RNA were investigated. Extensive cleavage of U1 RNA was observed with the unmodified oligodeoxynucleotide and with the phosphorothioate analogue but not with U1-complementary oligodeoxynucleotides containing methylphosphonate, phosphoro-N-morpholidate, or phosphoro-N-butylamidate internucleoside linkages. Additional experiments using a 514-nucleotide-long RNA substrate demonstrated the capacity of complementary phosphodiester- and phosphorothioate-linked oligodeoxynucleotides (but not ones containing methylphosphonate, phosphoro-N-morpholidate, or phosphoro-N-butylamidate linkages) to serve as RNase H targets when hybridized to an internal RNA site. Detailed comparisons revealed phosphodiester-linked oligodeoxynucleotides to be more efficient than the comparable phosphorothioate-linked oligomers with respect to RNase H action. Various pentadecamer oligodeoxynucleotides complementary to the 514-nucleotide-long test RNA and containing 2-6 consecutive phosphodiester- or phosphorothioate-linked nucleotides flanked by RNase H-resistant methylphosphonate linkages afforded precise "site-directed" RNase H excision within the DNA.RNA hybrid. These results serve to assort modified oligodeoxynucleotide-containing hybrids into RNase H-sensitive and -resistant classes and also provide clues as to how RNase H makes contact with the DNA strand in a DNA.RNA hybrid.